2013
DOI: 10.1080/02699931.2012.708648
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and use of perspective taking within a communicative context

Abstract: Individuals with moderate to high levels of depressive symptoms are more challenged by using a speaker's perspective to interpret statements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, both perspective taking and empathic concern have been related to multiple aspects of trait mindfulness [ 35 ], which is a protective factor from worry and anxiety during the COVID-19 outbreak [ 36 ]. On the other hand, a difficulty in completing tasks implying perspective taking has been observed in individuals scoring high on a measure of depressive symptoms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both perspective taking and empathic concern have been related to multiple aspects of trait mindfulness [ 35 ], which is a protective factor from worry and anxiety during the COVID-19 outbreak [ 36 ]. On the other hand, a difficulty in completing tasks implying perspective taking has been observed in individuals scoring high on a measure of depressive symptoms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, it may be that maladaptive perfectionists are as socially aware as adaptive perfectionists, but their perspectives may be clouded by self‐critical tendencies, and thus, their interpretations would be skewed toward perceived rejection or disapproval. As some supporting evidence, research has shown that individuals who are depressed, are anxious, or have low self‐esteem tend to make cognitive errors when interpreting the reactions others; attributing these actions with malevolent intent or as a reflection to their own deficiencies (e.g., Nilson & Duong, ; Wells & Papageorgiou, ; see also Marin & Miller, , for related discussions applied to adolescents). Extant studies consistently show that maladaptive perfectionists (compared with adaptive perfectionists and nonperfectionists) report significantly higher levels of psychological distress (see Gilman & Ashby, ; Lo & Abbott, ), and by virtue of these elevated negative states, maladaptive perfectionists may be more likely to “interpret others in their social worlds as dissatisfied with them and disapproving of them” (Sherry et al., , p. 696).…”
Section: Discussionmentioning
confidence: 99%
“…Of course this laboratory task surely overestimates the rate of errors in real discourse, not least because the design deliberately deprives participants of most cues that could enable them to be sensitive to perspective without representing the director's perspective. Nonetheless, these error rates are higher in participants with higher traits for autism and psychosis (Abu‐Akel, Wood, Hansen, & Apperly, ), self‐reported symptoms of depression (Nilsen & Duong, ), and induced positive mood (Converse, Lin, Keysar, & Epley, ), suggesting that they are a valid indicator of variation in social communication performance. Also error rates and/or other indices, such as decision time and rate of change in preference for the target compared with the distractor, are positively influenced by motivation and adversely influenced by concurrent working memory load (Cane et al., ; Lin, Keysar, & Epley, ) and the complexity of the director's instruction (Wang, Frisson, Ali, & Apperly, ).…”
Section: What Do We Know About Mindreading?mentioning
confidence: 99%